Efektivitas Sociopreneurship di Masa Transisi Covid-19 - Dinda Niken Pratiwi; Trisni Handayani (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2023)
The large number of sociopreneurships in Indonesia is still felt to be insufficient to fulfill government programs. Nara Synergy is here to be part of sociopreneurship in Indonesia. This study uses a qualitative research method, which is based on the philosophy of postpositivism. The analysis in this study discusses several research sub focuses including 1) the main factors of sociopreneurship, 2) sociopreneurship stakeholders, and 3) the effectiveness of sociopreneurship. The results of the research show that the Berkah Usaha Bersama (BUB) Garbage Bank has been running effectively in line to establish the Garbage Bank.